Development of novel degradable pH-responsiveness polymers for potential applications in 3D printing - Lu, Yu (2021)
Stimuli-responsive materials have been researched for decades, there are many forms of stimuli-responsiveness, such as pH-, light- and thermal-responsiveness among others. In addition, the use of degradable materials can expand the range of possible final applications, e.g., coating and drug delivery. 3D printing is a subset of rapid prototyping technologies, which is based on computer model files and bondable material (such as powder-like polymer) to fabricate objects via a layer-by-layer process, there are many related technologies, such as, inkjet printing and selective laser sintering (SLS). However, they suffer of key shortcomings based on the lack of functionalised available materials. For example, for SLS, limited polymers nature and restricted range of colours are reported for the production of the final printed objects. In this project, we designed and synthesized a series of coloured copolymers endowed with a further pH responsiveness, foreseeing pH and “sweat” sensors as possible final applications. Dispersed Red I and 4-phenylazophenol (yellow dye) have been selected as two of the three-primary colours. 2-hydroxyethyl methacrylate (HEMA), 2-hydroxyethyl acrylate (HEA), lactide and succinic anhydride were used as building blocks to synthesize macroinitiators with degradable features. The degradable moiety and colour groups were linked through a labile ester functionality. 1H NMR, FT-IR and GPC analysis were used to confirm the success of the reactions and the final molecular structures. Degradation test was set up in 1M H2SO4 and 1M NaOH aqueous environments. The colour change of the aqueous media can be observed when the colour moiety was cleaved and the decreasing in Mn was monitored by GPC.